Role of Coptis chinensis in antibiotic susceptibility of carbapenem-resistant Klebsiella pneumoniae - Cheng-Yin Tseng; Mao-Feng Sun; Tzu-Chien Kao; Tsai-Chung Li; Ching-Ting Lin (Journal of Microbiology, Immunology and Infection, 2022)
Background: The incidence of carbapenem-resistant Klebsiella pneumoniae (CRKP) has rapidly increased. This study aimed to assess the effect of Coptis chinensis and its compounds on the minimal inhibitory concentrations (MICs) of eight antibiotics against CRKP. Methods: Cell cultures were used to investigate the effects of C. chinensis and its compounds on the MICs of eight antibiotics against CRKP. The MICs for antibiotics alone and antibiotics with C. chinensis or compounds were measured and compared. Furthermore, the effects of C. chinensis on cell membrane injury and intracellular adenosine triphosphate (ATP) CRKP concentration were also measured. The Mann–Whitney rank-sum test was used to analyze the differences between means. Results: C. chinensis exhibits a notable MIC bacteriostatic effect at 5 mg/mL on CRKP. A significant MIC reduction against CRKP exists when C. chinensis was added to colistin and colistin-containing two-antibiotic combinations. Moreover, C. chinensis could damage cell membrane integrity and decrease intracellular ATP concentration in CRKP. Thus, C. chinensis exhibits antimicrobial activity superiority with colistin against CRKP. Furthermore, the effects of identified compounds in C. chinensis on the MICs of colistin, four-to eight-, two-to four-, and one-to two-fold reductions were found in ferulic acid, magnoflorine, and jatrorrhizine hydrochloride, respectively. Among these compounds, ferulic acid destroys membrane integrity and decreases intracellular ATP concentration. Conclusion: C. chinensis and ferulic acid can potentiate the antimicrobial activity of colistin and may represent a promising component of combination therapy against CRKP infections in a clinical setting.